Motivation and academic achievement: a case study of Malaysian aboriginal (Orang Asli) students - Che Hassan, Norlizah; Arumugam, Thava Malar (Human Resource Management Academic Research Society, 2017)
Study on the relationship between motivation and academic achievement is undoubtedly important, therefore this study aimed to identify the motivation level of Malaysian Aboriginal students and to investigate the relationship between motivation (intrinsic and extrinsic), academic achievement and economic status among Malaysian Aboriginal students in Kuala Langat, Selangor, Malaysia. The study was conducted amongst Aboriginal students from all secondary schools in Kuala Langat, Selangor from the age of 16 – 18 years. There were approximately 100 students in the population. 87.9 % of the respondents considered failed in PMR, 8.1% were moderate, meanwhile only 4.0% obtained good result. Majority of the respondents which is 56.6% of the sample obtained medium score (65-102), while 28.3 obtained low score (<65) and 15.2 % of the respondents obtained high score (>102). The result of the study indicated there is a relationship between intrinsic motivation (r = 0.571), extrinsic motivation (r = 0.506) and academic achievement. Finally, recommendations are given to parents, teachers and policymakers.